Analysis of Deixis in Short Story “A Little Match Girl”: Pragmastylistics Study - Ummi Salamah; Ika Octaviani; Nur Alfiana Isnaini (Vivid: Journal of Language and Literature, 2021)
This study has purposes to analyze and describe the language style used by Hans Christian Andersen in his short story entitled 'A Little Match Girl' by using pragmatic aspects that are carried out by analyzing deixis components in the story text. This research applied the descriptive qualitative design. By using pragmastylistics theory, this research focuses on the type of deixis used by the author in presenting his story which is then used to reveal the language style of the literary text. The data of this study were collected from deictic words used in the short story. The steps which are used by the researchers are begun from reading, taking notes, analyzing, categorizing and then summarizing the data. The results reveal five kinds of deixis consisting of person, time, place, social and discourse deixis were used in the text. From the data analysis, 97 deixis were found in total with 65 data of person deixis, 4 data of place deixis, 4 data of time deixis, 14 data of social deixis, and 10 data of discourse deixis. Finally, the most frequent deixis found in the short story is the person deixis, especially third-person deixis which indicates that the author of the short story used third-person point of view to convey his ideas in his short story.